Editorial: The new market challenges and the strategies of the wine companies - Silvio Menghini (Wine Economics and Policy, 2015)
In my new role as editor-in-chief of WEP Journal, I would like to share with you a brief summary of the experience of these early years. In this editorial, I will focus on certain significant data and highlight several topics that, more than others, have inspired the authors of the published papers, since they reflect the major concerns of the wine industry in this period.
Keywords: 330